Covid-19 pandemic lessons: uncritical communication of test results can induce more harm than benefit and raises questions on standardized quality criteria for communication and liability. Issue 1 (1st January 2021) - Porzsolt, Franz; Pfuhl, Gerit; Kaplan, Robert M.; Eisemann, Martin
ABSTRACT: Background: The COVID-19 pandemic is characterized by both health and economic risks. A 'safety loop' model postulates risk-related decisions are not based on objective and measurable risks but on the subjective perception of those risks. We here illustrate a quantification of the difference between objective and subjective risks. Method: The objective risks (or chances) can be obtained from traditional 2 × 2 tables by calculating the positive (+LR) and negative (−LR) likelihood ratios. The subjective perception of objective risks is calculated from the same 2 × 2 tables by exchanging the X- and Y-axes. The traditional 2 × 2 table starts with the hypothesis, uses a test and a gold standard to confirm or exclude the investigated condition. The 2 × 2 table with inverted axes starts with the communication of a test result and presumes that the communication of bad news (whether right or false) will induce 'Perceived Anxiety' while good news will induce 'Perceived Safety'. Two different functions (confirmation and exclusion) of both perceptions (Perceived Anxiety and Safety) can be quantified with those calculations. Results: The analysis of six published tests and of one incompletely reported test on COVID-19 polymerase chain reactions (completed by four assumptions on high and low sensitivities and specificities) demonstrated that none of these tests induces 'Perceived Safety'. Eight of the ten tests confirmed the induction of 'Perceived Anxiety' with + LRs (range 3.1–5900). In two of these eight tests, a −LR (0.25 and 0.004) excluded the induction of 'Perceived Safety'. Conclusions: Communication of test results caused perceived anxiety but not perceived safety in 80% of the investigated tests. Medical tests – whether true or false – generate strong psychological messages. In the case of COVID-19 tests may induce more perceived anxiety than safety. Risk communication has to balance objective and subjective risks.